Pemanfaatan AI untuk Meningkatkan Pemahaman Konsep Matematika di Era Digital (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
In recent years, technology, particularly artificial intelligence (AI), has played an important role in driving change in many fields, including education. As the digital era continues to evolve, the use of AI in mathematics learning offers a great opportunity to improve the way students understand and master mathematical concepts that are often considered challenging. This paper is based on a literature review that discusses how AI can play a role in creating more adaptive, interactive and data-driven mathematics learning. Several studies have shown that AI can facilitate dynamic math simulations, support personalized learning approaches, and provide instant feedback that helps accelerate the learning process. In addition, this paper also highlights the potential of AI in addressing gaps in understanding between students as well as limitations in conventional learning. The application of AI in education also faces a number of challenges, including technological challenges, ethical issues, and protection of student data. This paper also explores opportunities for further development of AI in education, especially in mathematics learning. With effective implementation, AI is expected to become an innovative tool that plays a major role in improving the understanding of mathematical concepts, as well as overcoming educational challenges in the digital era